Automatic Enhancement Of Digital Images Using Cubic BÃ©zier Curve And Fourier Transformation - Asghar, Khurshid; Gilanie, Ghulam; Saddique, Mubbashar; Habib, Zulfiqar (Malaysian Journal of Computer Science, 2017)
Image enhancement is one of the most important and visually appealing areas of digital image processing and computer vision. It is considered as a very important part of pre-processing for the development of industrial, security, forensic, medical, and many other applications. Although significant efforts were devoted in the past, a completely automatic image enhancement for all types of input and applications is still a big challenge in the domain of image processing. In this paper, we have proposed a multi-disciplinary approach to enhance the image automatically by intensity transformation in the spatial domain through cubic BÃ©zier curve on images filtered with low and high pass Butterworth in the frequency domain. Results are promising when compared with the existing state-of-the-arts techniques for both visually and quantitatively, which proved that the proposed method can ensure better contrast enhancement.